To simplify the expression \( 10x + 3(x - 15) \) using the Distributive Property, follow these steps:
-
Distribute the \( 3 \) to both terms inside the parentheses: \[ 3(x - 15) = 3 \cdot x - 3 \cdot 15 = 3x - 45 \]
-
Now, replace \( 3(x - 15) \) in the original expression: \[ 10x + 3(x - 15) = 10x + 3x - 45 \]
-
Combine the like terms \( 10x \) and \( 3x \): \[ 10x + 3x = 13x \]
-
So, the expression becomes: \[ 13x - 45 \]
Therefore, the simplified expression is \( 13x - 45 \).
The correct response is 13x minus 45.